The socioeconomic impacts of low income housing programs in S\~ao Paulo state, Brazil - Rodger Campos; Joaquim Guilhoto (European Regional Science Association (ERSA), 2016)
The state programs for low income housing in Brazil started in the 1930s, and most recently the well-advertised program 'My House, My Life' by the Federal government had on its goals to improve the quality of life of poor people, to reduce the housing deficit and to foster the economy. The question raised by this paper is how important was the contribution of the program for the economic growth observed in the Brazilian economy in previous years? In a way to shed light on this question, the case of the low income housing programs in the state of S\~ao Paulo is taken as an example. The State program being a joint venture among the federal, state and municipal governments. To do so, a specific interregional input-output model is estimated for two regions, S\~ao Paulo and Rest of Brazil, with the insertion in the model of 5 different typologies of low income housing, ranging from a single house to building complexes. The impacts are measured in terms of GDP, tax collection and employment in the State of S\~ao Paulo and in the Rest of Brazil, showing that depending on the housing typology, the impacts in the economy are different, and that part of the investments made returns to the government in terms of tax collection.
Keywords: R30; R15; 330; Low Income Housing; Input-Output; Brazil; S\~ao Paulo State